Age and environmental factors predict psychological symptoms in adolescent refugees during the initial post-resettlement phase - Debbie C. Hocking; Suresh Sundram (BMC, 2022)
Abstract Background Adolescent refugees are at high risk of developing mental disorders but are often not recognised early. This pilot study aimed to identify early putative risk factors associated with psychological symptoms in newly resettled refugee youth at potential risk of subsequently developing mental disorders. Methods Newly resettled adolescent refugees were recruited through English language schools in Melbourne, Australia. Participants were assessed with the MINI-Kid, Achenbach Youth Self-Report and Reaction of Adolescents to Traumatic Stress scale. Parents completed a mental health screening separately. Linear regression models were used to identify predictive factors associated with symptom ratings. Results Seventy-eight, ostensibly well, refugee adolescents (mean age = 15.0 ± 1.6 years) resettled in Australia for 6.1 ± 4.2 months were assessed. Levels of anxiety, depression and post-traumatic stress symptoms were considerably lower than in mainstream population data. Prior displacement was a key determinant of symptomatology. Transitory displacement, irrespective of duration, was associated with elevated scores for depression (t (47) = -4.05, p < 0.0001), avoidance/numbing (U = 466, p < .05) and total trauma (U = 506, p < .05) symptoms. Older age was a unique predictor of depression (F (1,74) = 8.98, p < .01), internalising (F(1,74) = 6.28, p < .05) and total (F(1,74) = 4.10, p < .05) symptoms, whilst parental depression symptoms (t = 2.01, p < 0.05), displacement (t = 3.35, p < 0.01) and, expectedly, trauma exposure (t = 3.94, p < 0.001) were unique predictors of post-traumatic stress symptoms. Conclusions Displaced status, older age, and parental symptoms predicted psychological symptoms in adolescent refugees in an initial relatively asymptomatic post-resettlement phase. The early recognition of at-risk refugee youth may provide an opportunity for preventative mental health interventions.